Design of a novel wireless power transfer technique for portable device. (2022) - Nandakumar, S.; Gunasekaran, S.; Mohan Das, R.; Bharatiraja, C.
Highlights: The following are the few key highlights of this manuscript. This paper introduced the concept of inductive and lighting effects to build a novel wireless power transfer technique for portable devices. A Proposed technique analysed the performance of the copper and aluminium materials based multi-loop coil system in receiver side of WPT. The proposed system included a IoT based Battery Management System (BMS) that monitors the voltage, temperature, battery state of charge (SoC) and cell balancing of the battery and also the battery monitoring parameters stored in cloud environment. The simulation is carried out in Ansys software to analyse the flux distribution and identify optimal distance between transmitter and receiver. Abstract: In this paper, the concept of inductive and lighting effects has been introduced to build a wireless power transfer technique for portable devices. For high efficient operation of the overall system, the receiver side has a tiny PV array and a multi loop magnetic coil. A multi-loop coil system was employed in the receiver side, and low-power–high lumen LEDs were used in the transmitter, to increase the system's performance. The LED magnifier configuration aids in the illumination of a larger region. Using a magnetic coil and a photovoltaic array, alternating electromagnetic fields and light signals were transformed back into electrical impulses. Induced voltage in the receiver coil is converted to DC signal with the help of a rectifier. DC voltage can be directly received from the PV array. The Lithium ion battery has been used to store these DC signals. The system also includes a IoT based Battery Management System (BMS) that monitors the voltage, temperature, battery state of charge (SoC), and cell balancing of the battery. In order to evaluate the performance of the system, experimental circuit has been built and tested with multi coils and PV arrays used in receiver side.